Analysis of the Socio-Economic Impact on Early Marriage in Pohon Batu Village, Waesama District, South Buru Regency - Mamulaty, Karmila; Riry, Roberth Berthy; Leuwol, Ferdinand Salomo (Jurnal Pendidikan Geografi Unpatti, 2024)
Marriage is an institution that binds two individuals in a legally recognized relationship by religion, law, and custom. It is a crucial foundation for building a happy and sustainable family life. However, early marriage, particularly below the age of 20, poses serious challenges. Teenagers who marry too young are often unprepared for the responsibilities of marriage and are at risk of health and economic problems. This issue occurs across Indonesia, reflecting the complexity of social and financial difficulties. Preventive measures and vital interventions are needed to address early marriage and improve community welfare. Qualitative descriptive research in Pohon Batu Village, South Buru Regency, employs interviews, observations, and data analysis. This research explores the socioeconomic factors influencing early marriage by combining qualitative and quantitative methods. It aims to provide a holistic understanding for developing more effective policies. Early marriage has severe implications for individuals and society, as social and economic factors and parental influence influence it. Children or teenagers who marry young are at risk of health, education, and financial problems, exacerbating poverty and gender inequality. Improving education, empowering women, and economic development are needed to reduce early marriage and address its impact appropriately.